TRADISI NGEJOT SEBAGAI MEDIA KOMUNIKASI ANTAR UMAT BERAGAMA - Masuratun Hidayah; Shinta Nurrohmah; Mochamad Aris Yusuf (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
Bali is an area with a diverse population, including Plurality which provides a dynamic, harmonious and tolerant life order, while communication is a human need. So this article aims to answer the problem of how the ngejot tradition is used as a medium of communication between religious communities. The research method in this article uses qualitative methods and a case study approach, the subjects in this study are the people in Buleleng district. The results in this study have shown that Balinese people are very thick with the ngejot tradition as an expression of harmonious relations between religious communities as a means of tolerance to create harmony between religious communities, because community tolerance is based on individual and group participation in the same activities and responsibilities. so that it is clear that the various religions actually practice goodness.